Decreased Length of Stay After Laparoscopic Diaphragm Repair for Isolated Diaphragm Injury After Penetrating Trauma. Issue 5 (May 2020) - Chaudhry, Haris H.; Grigorian, Areg; Lekawa, Michael E.; Dolich, Matthew O.; Nguyen, Ninh T.; Smith, Brian R.; Schubl, Sebastian D.; Nahmias, Jeffry T.
Background: Isolated diaphragm injury (IDI) occurs in up to 30% of penetrating left thoracoabdominal injuries. Laparoscopic abdominal procedures have demonstrated improved outcome including decreased postoperative pain and length of stay (LOS) compared to open surgery. However, there is a paucity of data on this topic for penetrating IDI. The aim of this study was to examine the prevalence and outcome of laparoscopic diaphragmatic repair versus open diaphragmatic repair (LDR vs ODR) of IDI. Methods: The Trauma Quality Improvement Program (2010-2016) was queried for patients with IDI who underwent ODR versus LDR. A bivariate analysis using Pearson chi-square and Mann-Whitney test was performed to determine LOS among the two groups. Results: From 2039 diaphragm injuries, 368 patients had IDI; 281 patients (76.4%) underwent ODR and 87 (23.6%) underwent LDR. Compared to LDR, the ODR patients were older (median, 31 vs 25 years, P < .001) and had a higher injury severity score (mean, 11.2 vs 9.6, P = .03) but had similar rates of intensive care unit LOS, unplanned return to the operating room, ventilator days, and complications ( P > .05). Patients undergoing ODR had a longer LOS (5 vs 4 days, P = .01), compared to LDR. There were no deaths in either group. Conclusions: Trauma patients presenting with IDI undergoing ODR had a longer hospital LOS compared to patients undergoing LDR with no difference in complications or mortality. Therefore, we recommend when possible an LDR should be employed to decrease hospital LOS. Further research is needed to examine other benefits of laparoscopy such as postoperative pain, incisional hernia, and wound-related complications.